2008
DOI: 10.1063/1.2961029
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic, structural, and dynamic properties of supercooled water confined in mesoporous MCM-41 studied with calorimetric, neutron diffraction, and neutron spin echo measurements

Abstract: Thermodynamic, structural, and dynamic properties of heavy water (D(2)O) confined in mesoporous silica glass MCM-41 C10, C12, and C14 were investigated by differential scanning calorimetry, neutron diffraction, and neutron spin echo (NSE) measurements, respectively. The DSC data showed that no crystallization of D(2)O confined in C10 occurs in a temperature range between 298 and 180 K, and that crystalline ice is formed at 204 and 221 K for C12 and C14, respectively. For C10, the neutron radial distribution fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
119
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(139 citation statements)
references
References 37 publications
19
119
0
Order By: Relevance
“…Inelastic neutron experiments to study water dynamics were performed in the late 1950s, close to the very beginning of neutron beam applications to the study of liquids 2,3 and neutrons continue to contribute significantly in the field, the study by ref. 4 being a recent example.…”
Section: Neutronsmentioning
confidence: 99%
“…Inelastic neutron experiments to study water dynamics were performed in the late 1950s, close to the very beginning of neutron beam applications to the study of liquids 2,3 and neutrons continue to contribute significantly in the field, the study by ref. 4 being a recent example.…”
Section: Neutronsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Important findings from these studies are the supercooling of water, retardation of the motion of water molecules, distortion of tetrahedral-like hydrogen-bonded structure of water, and a fragile-to-strong dynamical crossover at around 220 K in confinement. Most of confined systems employed in previous studies were mesoporous materials, such as Vycor, 1,4,5 MCM-41, 3,6,[7][8][9][10][11][15][16][17][18][19] carbon nanotube 12 and activated carbon. 13,14 However, these materials have hard walls.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the thermal property and structure of confined water have drawn much attention for understanding the underlying mechanism of processes in confined systems. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] One of the recent topics of confined water is related to the fact that water confined in pores whose diameter is less than ~20 Å is not frozen in a temperature range of 235 -150 K, 7,8,[10][11][12][13][14][15][16][17][18][19] the so-called no-man's land, 20 where bulk water is always frozen below the homogeneous nucleation temperature (235 K) of water. Unfrozen water is particularly important, since it would provide us a key for understanding anomalous properties of water, the separation of solutes in chromatography, the survival of plants and insects under extreme conditions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Recent spectroscopic studies have reported that water molecules confined in pores smaller than 2 nm do not freeze even around 200 K and the transition from high-density to lowdensity hydrogen bonding structures occurs. [21][22][23][24][25] The slowing down of both rotational and/or translational motions of confined water molecules has been also verified to be promoted with decreasing pore sizes and temperatures. [26][27][28][29] These results have suggested that the specific hydrogen bonding network of water layer on surfaces differing from bulk water, i.e., the adsorbed water phase, is responsible for causing the freezing behavior of confined water in the supercooled state.…”
Section: Introductionmentioning
confidence: 99%